Assessment of the impact of terrorism on tourism in the 21st century: the example of Egypt - Ziółkowska-Weiss, Kamila; Pieron, Emilia (Przedsiębiorczość - Edukacja, 2021)
The article aims to analyse the impact of terrorism in Egypt on its tourism sector. To investigate the topic and obtain an answer to the research thesis that terrorism threat affects the level of tourism in Egypt, a literature review was used, and research was carried out in the form of an online questionnaire. The concept of terrorism is defined, and its types, causes and characteristics are shown through specific examples. The research has shown that terrorist threats perceived by tourists have a significant impact on their decisions when choosing a tourist destination. It shows that 36% of the respondents checked the current political situation of the chosen destination long before the planned departure, and 55% did it shortly before leaving.